Greenwash, show your true colours: how verbal and visual messages influence consumers' perception?. (3rd February 2023) - Basso, Kenny; Pauli, Jandir; Cerutti, Priscila; Perin, Marcia; Corte, Vitor Francisco Dalla; Moro, Leila Dal
There is a gap between information on green products or cleaner production presented by the companies using verbal and visual messages and the consumer's perception. In this respect, the current research aims to verify how verbal and visual messages differently influence consumers perceptions of greenwash in an advertisement. A single factor experiment was designed. The results indicate that people exposed to the text format presented a lower elaboration (M = 3.75) than the subjects exposed to the image format (M = 4.91). The communication through an image created a more suspicious and negative word of mouth about the text format. In this way, an image may require a level of cognitive effort that can harm the greenwash perception.